PENGARUH APLIKASI TAM DAN KEPERCAYAAN TERHADAP MINAT MAHASISWA MEMBELI ULANG MENGGUNAKAN E-COMMERCE DALAM PEMBELIAN PRODUK PAKAIAN DAN AKSESORIS - Nangi, Iman Yosafat; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen, 2015)
This study aimed to determine the effect tam applications and trust in the interest of students using e-commerce in the purchase of clothing and accessories at the Faculty of Economics and Business, University of Udayana. The data analysis technique used is the method of analysis of Multiple Linear Regression (Multiple Linear Regression). The results of this study indicate that the usefulness, ease of use, and trust simultaneously positive and significant effect on the interest in using e-commerce in the regular program students of the Faculty of Economics and Business, University of Udayana. Based on the research of e-commerce services managers to pay attention to e-commerce transactions to be more accelerated in order to deal more effectively. Managers also must maintain the grammar, the reputation of the website, as well as check feature in the transaction so that more people use the services of e-commerce.
Keywords: aplikasi TAM; kepercayaan; minat membeli ulang menggunakan e-commerce; produk pakaian; aksesoris